Efficacy and safety of leuprorelin (Boennuokang®) plus endocrine therapy in premenopausal women with HR+/HER2− breast cancer - Wu, Xiuping; Lin, Yinfeng; Xie, Wangmei; Jiang, Yan; Xu, Zhenchao; He, Kai; Li, Shuyu (Frontiers in Pharmacology, 2025)
BackgroundLeuprorelin shows good efficacy in premenopausal women with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) breast cancer. However, more real-world evidence is required. This real-world study aimed to explore the efficacy and safety of leuprorelin (Boennuokang®) plus endocrine therapy in premenopausal women with HR+/HER2− breast cancer.MethodsA total of 229 premenopausal women with HR+/HER2− breast cancer receiving adjuvant leuprorelin plus endocrine therapy were included in this retrospective study. Leuprorelin (Boennuokang®) was administered 3.75 mg subcutaneously every 28 days following surgery. Endocrine therapy contained aromatase inhibitors, selective estrogen receptor modulators, and selective estrogen receptor degraders. The median follow-up duration of this study was 38.1 months.ResultsThe estradiol (E2) level was declined from 46.0 to 19.0 pg/mL over 24 months (P < 0.001). E2 from month 3 to month 24 was maintained below 30 pg/mL (menopausal level). During 24 months, the follicle-stimulating hormone level was decreased from 7.7 to 4.8 mIU/mL, and the luteinizing hormone level was decreased from 7.9 to 0.2 mIU/mL (both P < 0.001). During the follow-up period, 9 patients experienced disease recurrence. The 10-year accumulating progression-free survival (PFS) rate was 91.7%. Comorbidity (yes vs no) was independently related to shorter progression-free survival (hazard ratio: 10.957, P = 0.003). Bone soreness (6.1%) was the most common adverse event, followed by hot flushes (3.5%), morning stiffness (1.3%), and muscle soreness (1.3%).ConclusionLeuprorelin (Boennuokang®) plus endocrine therapy reduces gonadotropins and sex hormones and results in satisfactory survival rates with good safety profiles in premenopausal women with HR+/HER2− breast cancer.